2016
DOI: 10.1002/ar.23495
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Magnetic Resonance Imaging Identification of Thoracolumbar Spine Variants with Implications for the Positioning of the Conus Medullaris in Rhesus Macaques

Abstract: The anatomy of the vertebral column in mammals may differ between species and between subjects of the same species, especially with regards to the composition of the thoracolumbar spine. We investigated, using several noninvasive imaging techniques, the thoracolumbar spine of a total of 44 adult rhesus macaques of both genders. Radiographic examination of the vertebral column showed a predominant spine phenotype with 12 rib-bearing thoracic vertebrae and 7 lumbar vertebrae without ribs in 82% of subjects, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It may not be surprising that the relative hot spot locations for LUT functions showed relatively extensive inter-individual variation in the present study, as the vertebral level for the location of the tip of the conus medullaris varied extensively between humans in clinical studies (Saifuddin et al, 1998;Wilson and Prince, 1989). Recent magnetic resonance imaging studies of rhesus macaques demonstrated a similar variation with regards to the rostro-caudal positioning of the sacral spinal cord with the rostral and caudal extent of the conus medullaris at 2.0 ± 0.3 and 3.6 ± 0.4 vertebral units below the thoracolumbar junction, respectively (Ohlsson et al, 2017). An additional potentially confounding factor for TSCS in rhesus macaques is the presence of a set of supernumerary ribs at the L1 vertebra in about 20% of subjects (Ohlsson et al, 2017).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It may not be surprising that the relative hot spot locations for LUT functions showed relatively extensive inter-individual variation in the present study, as the vertebral level for the location of the tip of the conus medullaris varied extensively between humans in clinical studies (Saifuddin et al, 1998;Wilson and Prince, 1989). Recent magnetic resonance imaging studies of rhesus macaques demonstrated a similar variation with regards to the rostro-caudal positioning of the sacral spinal cord with the rostral and caudal extent of the conus medullaris at 2.0 ± 0.3 and 3.6 ± 0.4 vertebral units below the thoracolumbar junction, respectively (Ohlsson et al, 2017). An additional potentially confounding factor for TSCS in rhesus macaques is the presence of a set of supernumerary ribs at the L1 vertebra in about 20% of subjects (Ohlsson et al, 2017).…”
Section: Discussionsupporting
confidence: 49%
“…Recent magnetic resonance imaging studies of rhesus macaques demonstrated a similar variation with regards to the rostro-caudal positioning of the sacral spinal cord with the rostral and caudal extent of the conus medullaris at 2.0 ± 0.3 and 3.6 ± 0.4 vertebral units below the thoracolumbar junction, respectively (Ohlsson et al, 2017). An additional potentially confounding factor for TSCS in rhesus macaques is the presence of a set of supernumerary ribs at the L1 vertebra in about 20% of subjects (Ohlsson et al, 2017). This anatomical spine variant will likely influence placement of surface electrodes, providing an obvious advantage of the present non-invasive approach compared to a permanently implanted array.…”
Section: Discussionmentioning
confidence: 82%
“…These maps demonstrate that organized, compact motor networks exist in the lumbosacral spinal cord of rhesus monkeys which may be targeted to restore lower limb mobility. Despite the natural variability of the number of lumbar vertebral segments in the studied animals 33,34 , the relative organization of the motor networks in the obtained functional maps was consistent from one animal to another. In all animals, hip flexors were activated in more rostral regions of the lumbar enlargement than knee extensors, followed by ankle flexors, hip extensors, toe flexors, ankle extensors, extensor synergy, knee flexors, and backward synergy.…”
Section: Discussionmentioning
confidence: 75%
“…In humans, magnetic resonance imaging (MRI) studies have shown that the location for the tip of the conus may range from the T 11 /T 12 to L 2 /L 3 vertebrae levels (Morimoto et al 2013;Wilson and Prince 1989). In rhesus macaques, recent MRI studies have shown that the conus medullaris tapers over a length of 1.5 Ϯ 0.3 vertebral units, with the top and tip of the conus medullaris at 2.0 Ϯ 0.3 and 3.6 Ϯ 0.4 vertebral units from the thoracolumbar junction, respectively (Ohlsson et al 2017). This anatomical feature of the lumbosacral spinal cord provides a rationale for some of the observed intersubject variability related to the most optimal TSCS location for the activation of peripheral target responses.…”
Section: Discussionmentioning
confidence: 99%